Isolation and Screening Microorganisms from Black Soldier Fly Larvae (Hermetia illucens) that Producing Amylase, Protease and Cellulase - Dalia Sukmawati; Rheva Amadea; Putri Novitasari; Yohana Caroline Sihombing; Axel Mareta; Yohannes Eka Cordias Buulolo; Atin Supiyani; Muktiningsih Nurdjayadi; Diat Nurhidayat; Roshanida A. Rahman; Sulistiyani; Raden Haryo Bimo Setiarto (Postgraduate, University of Mataram, 2023)
The Black Soldier Fly (BSF) has gained significant attention for its ability to decompose various types of organic waste and produce valuable enzymes related to its digestive system. These enzymes hold immense potential for applications across diverse industrial sectors, with promise in the livestock industry. This study aimed to extract and assess amylase, protease, and cellulase enzymes from microorganisms present in BSF larvae fermentation. The isolation technique employed was the spread plate method, followed by rigorous screening for the presence of these enzymes. The results showed 46 isolates of 26 bacterial isolates and 20 yeast isolates. In the amylase enzyme screening, a substantial 25 bacterial and 19 yeast isolates exhibited positive amylase activity. For cellulase, 20 bacterial and 14 yeast isolates displayed positive results. In the case of protease, 16 bacterial and 12 yeast isolates demonstrated protease enzyme activity. Notably, nine isolates exhibited the remarkable capability to produce multiple enzymes, including eight bacterial and one yeast isolate. These results showcase the rich enzymatic potential of BSF-associated microorganisms, offering exciting prospects for their application in various industrial sectors, especially in enhancing the efficiency and sustainability of livestock production